2006
DOI: 10.1073/pnas.0603968103
|View full text |Cite
|
Sign up to set email alerts
|

Reversible lysine acetylation controls the activity of the mitochondrial enzyme acetyl-CoA synthetase 2

Abstract: We report that human acetyl-CoA synthetase 2 (AceCS2) is a mitochondrial matrix protein. AceCS2 is reversibly acetylated at Lys-642 in the active site of the enzyme. The mitochondrial sirtuin SIRT3 interacts with AceCS2 and deacetylates Lys-642 both in vitro and in vivo. Deacetylation of AceCS2 by SIRT3 activates the acetylCoA synthetase activity of AceCS2. This report identifies the first acetylated substrate protein of SIRT3. Our findings show that a mammalian sirtuin directly controls the activity of a meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
558
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 642 publications
(580 citation statements)
references
References 40 publications
13
558
1
2
Order By: Relevance
“…Importantly, in mice the only form of SirT3 corresponds to the human processed protein. Both forms of the protein are enzymatically active in the NER assay and both deacetylate H4K16Ac and H3K9Ac in vitro (Scher et al, 2007), whereas the mitochondrial SirT3 protein targets AceCS2, as mentioned above (Schwer et al, 2006). Surprisingly, the global levels of H4K16Ac and H3K9Ac were found to be unaffected in cells knocked down in SirT3 levels by RNAi or in SirT3 À/À MEFs (Scher et al, 2007).…”
Section: Sirt3mentioning
confidence: 89%
See 1 more Smart Citation
“…Importantly, in mice the only form of SirT3 corresponds to the human processed protein. Both forms of the protein are enzymatically active in the NER assay and both deacetylate H4K16Ac and H3K9Ac in vitro (Scher et al, 2007), whereas the mitochondrial SirT3 protein targets AceCS2, as mentioned above (Schwer et al, 2006). Surprisingly, the global levels of H4K16Ac and H3K9Ac were found to be unaffected in cells knocked down in SirT3 levels by RNAi or in SirT3 À/À MEFs (Scher et al, 2007).…”
Section: Sirt3mentioning
confidence: 89%
“…The best studied is SirT2, the orthologue of yeast Hst2, that is involved in cell-cycle control and regulation of the cytoskeleton (discussed below). SirT3, the closest Sirtuin to SirT2, is found in mitochondria and so far only one mitochondrial target has been identified, AceCS2 (Schwer et al, 2006). However, full-length SirT3 is found in the nucleus, it seems to target histones and is shuttled to the mitochondria under conditions of stress ( Figure 4a); this nuclear function of SirT3 needs to be addressed further (Scher et al, 2007;see below).…”
Section: Class III Functionsmentioning
confidence: 99%
“…SIRT3 functions as a protein deacetylase (Onyango et al, 2002;Schwer et al, 2002), and specifically targets K642 of the mitochondrial protein acetyl-CoA synthetase 2. Deacetylation of acetyl-CoA synthetase 2 activates the enzyme and promotes the production of acetyl-CoA (Hallows et al, 2006;Schwer et al, 2006). Several genetic studies have linked SIRT3 to aging, including in humans (Rose et al, 2003;Glatt et al, 2007).…”
Section: Mitochondrial Sirtuins: Sirt3 Sirt4 and Sirt5mentioning
confidence: 99%
“…Rapid progress in the discovery and functional analysis of an increasing number of nuclear enzymes involved in protein lysine acetylation and deacetylation, histone acetyltransferases (HATs) and histone deacetylases (HDACs), respectively, have demonstrated that these enzymes, independently of transcription, can control some of the basic cellular processes such as protein stability (reviewed in Caron et al, 2005). Moreover, it is now clear that acetylation is not an exclusive modification of nuclear proteins, since many cytoplasmic proteins, including a significant subset of mitochondrial proteins, have recently been shown to bear lysine acetylation (Cohen et al, 2004;Dihazi et al, 2005;Iwabata et al, 2005;Kovacs et al, 2005;Hallows et al, 2006;Kim et al, 2006;Schwer et al, 2006). The regulation of these acetylations and the determination of their functional significance now constitute a real challenge for biologists.…”
Section: Introductionmentioning
confidence: 99%